THE IMPORTANCE OF INTERNATIONAL EXPERIENCE AND MODERN TECHNOLOGIES IN THE FIELD OF LABOR PROTECTION. (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article briefly describes the importance and convenience of international experience and modern technologies in the field of labor protection, including the creation of healthy work activities that meet world standards.